Research on Creep Characteristics and the Model of Artificial Frozen Soil - Chaochao Zhang; Dongwei Li; Changtai Luo; Zecheng Wang; Guanren Chen (Advances in Materials Science and Engineering)
To study the long-term stability of the large-scale freezing project, the longest subway connecting channel constructed by the artificial freezing method in China is taken as the background. The uniaxial compressive strength test, triaxial shear test, and triaxial creep test of artificial frozen soil under different temperatures were carried out by using the MTS 370.25 mechanical testing machine. A series of triaxial creep tests for artificial frozen soil under different stresses and temperatures were carried out. Based on the creep test results, a fractional-order constitutive model of frozen silt with sand was proposed. Comparing the calculated results with the tested ones, it is found that the proposed fractional-order model can simulate the properties of frozen silt with sand very well. Compared with the other creep models of frozen soil, the proposed model here has higher accuracy and strong stress sensitivity. Through the simulation of the connecting channel construction and comparison with the observed data in site, the effectiveness of the model is verified, which further verifies that the model has important guiding significance for the freezing project.